Transcriptome analysis identifies LGP2 as an MDA5-mediated signaling activator following spring viremia of carp virus infection in common carp (Cyprinus carpio L.) - Liu, Rongrong; Niu, Yan; Qi, Yue; Li, Hua; Yang, Guiwen; Shan, Shijuan (Frontiers in Immunology, 2022)
The common carp (Cyprinus carpio L.) is an important farmed species worldwide. Mucosal-associated lymphoid tissues play an essential role in the fight against pathogen infection. Spring viremia of carp virus (SVCV) poses a serious threat to the common carp aquaculture industry. Understanding the molecular mechanisms driving mucosal immune responses to SVCV infection is critical. In this study, the mucosal tissues (gills, foregut and hindgut) were collected from normal and infected fishes for transcriptome analysis. A total of 932,378,600 clean reads were obtained, of which approximately 80% were successfully mapped to the common carp genome. 577, 1,054 and 1,014 differential expressed genes (DEGs) were identified in the gills, foregut and hindgut, respectively. A quantitative polymerase chain reaction assay indicated that the DEGs expression in the foregut following SVCV infection was consistent with the transcriptome results. Among them, two key genes of the retinoic acid-inducible gene I (RIG-I)-like receptor family, melanoma-differentiation-associated gene 5 (MDA5) and laboratory of genetics and physiology 2 (LGP2) (i.e., CcMDA5 and CcLGP2), underwent further analysis. Overexpression of CcMDA5 or CcLGP2 increased phosphorylation of TANK-binding kinase 1 and interferon regulatory factor 3 and the expression of interferon-1 (ifn-1), myxovirus resistance (mx), viperin and interferon-stimulated gene 15 (isg15), and inhibited SVCV replication in epithelioma papulosum cyprini cells. Furthermore, CcLGP2 significantly upregulated the CcMDA5-induced ifn-1 mRNA expression and the activation of the ifn-1 promoter. Finally, confocal microscopy and coimmunoprecipitation experiments revealed that CcLGP2 colocalizes and interacts with CcMDA5 via the C-terminal regulatory domain. This study provides essential gene resources for understanding the fish immune response to SVCV infection and sheds light on the potential role of fish LGP2 in the MDA5 regulation.